Implementasi Low Power Mode Pada Sistem Keamanan Ignition Coil Breaker Sepeda Motor dengan Pengenalan Sidik Jari - Belsazar Elgiborado Giovani Djoedir; Dahnial Syauqy; Hurriyatul Fitriyah (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The development of science and technology is increasing and generate many advantages. In the other hand, criminal offense also increasing such as motorcycyle theft where the criminal subject take action by using the T key and chemical liquids. As the result based on this problem, the idea to make biometric security for motorcycle using fingerprint sensor by applying low power appeared. This security system is constructed using the R305 fingerprint sensor as the input to detect the user's fingerprint and register the fingerprint's user to its memory, arduino nano v3.0 as the microcontroller to process data from the fingerprint sensor and relay module as a switch that connected to the ignition coil system on the motorcycle. This system is also supported with wake and sleep feature with external interrupt in the form of push button to trigger wake condition from sleep. From the test a fingerprint sensor successfully perform enroll and authentication. From the test also obtained a decrease in current consumption used by system and reach 32.95%, when the relay module is active and 51.92% when relay module is inactive. In addition, the test results show that the system takes an average time of 134.2 milliseconds for wake from sleep condition.`